Prognostic Significance of Risk Factors and Biomarkers in Patients Hospitalized for Cardiorenal Syndromes: A Pilot Study - Theofilis, Panagiotis; Vordoni, Aikaterini; Nakas, Nikos; Kotsakis, Athanasios; Kranidis, Athanasios; Makryniotou, Ioanna; Kalaitzidis, Rigas G. (Current Medicinal Chemistry, 2023)
Background: Cardiorenal syndromes (CRS), involving the heart-kidney cross-talk and the activation of neurohumoral and inflammatory pathways, are an entity characterized by high morbidity and mortality. Objective: To evaluate the prognostic role of risk factors and biomarkers in patients hospitalized for CRS. Methods: In this observational cohort study, 100 consecutive patients hospitalized for CRS were enrolled. Socio-demographic characteristics, personal medical history, and prior medication use were recorded upon admission, and echocardiography was performed. Moreover, an array of blood markers were measured. The endpoint of interest was a composite of death or dialysis dependence at discharge. Results: Patients were classified into two groups; Group 1 (N= 52): discharged being dialysis-independent, Group 2 (N=48): death/dialysis dependence at discharge. No significant differences were detected in baseline characteristics between the two groups. Group 2 patients used renin-angiotensin-aldosterone system blockers (RAASb) less often and more frequently presented with oliguria/anuria. Group 2 patients had significantly lower hemoglobin, serum albumin, and 25-hydroxy-vitamin D (25(OH)D). At the same time, serum phosphate, potassium, and parathyroid hormone (PTH) were significantly higher in Group 2 patients. In a multivariate regression analysis, lack of prior RAASb and lower 25(OH)D levels were independently associated with an increased risk of death or dialysis dependence at discharge. 25(OH)D/PTH ratio was the most accurate predictor of the composite endpoint (Sensitivity: 79.4%, Specificity: 70.4%). Conclusion: Lack of prior RAASb use, high PTH, low 25(OH)D levels, and low 25(OH) D/PTH ratio are associated with a poor prognosis in patients hospitalized for CRS.
Keywords: heart failure